2018
DOI: 10.1177/0883073818809831
|View full text |Cite
|
Sign up to set email alerts
|

Serum Interleukin-6 Level in Children With Attention-Deficit Hyperactivity Disorder (ADHD)

Abstract: Introduction: Attention-deficit hyperactivity disorder (ADHD) is a common neurobehavioral disorder in children, but its specific etiology and pathophysiology are still incompletely understood. Objectives: This case-control study aimed to measure the level of serum interleukin-6 (IL-6) as a predictor of the immunologic status in children with ADHD, and to study its correlation with severity of symptoms. Subjects and Methods: 60 ADHD children who met the Diagnostic and Statistical Manual of Mental Disorders, 5th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 27 publications
4
38
1
Order By: Relevance
“…There are different results in the studies investigating the relationship between ADHD and inflammation in the literature. In cytokine studies, IL-6 levels were found to be higher in ADHD patients, but not correlated with ADHD severity (16). In another study, IL-6, IL-10, and anti-YO antibodies reported to be significantly higher in ADHD (10).…”
Section: Discussionmentioning
confidence: 93%
“…There are different results in the studies investigating the relationship between ADHD and inflammation in the literature. In cytokine studies, IL-6 levels were found to be higher in ADHD patients, but not correlated with ADHD severity (16). In another study, IL-6, IL-10, and anti-YO antibodies reported to be significantly higher in ADHD (10).…”
Section: Discussionmentioning
confidence: 93%
“…Recent evidence suggests that patients with ADHD have higher serum cytokine levels than controls. 9,11,32,33 Galectin-3 was suggested to lead to increased inflammatory response by suppressing the anti-inflammatory cytokine interleukin-10 (IL-10) production. 34 An in vitro survey also documented that galectin-3 induces IL-6 expression, while galectin-3 inhibition decreases IL-1β expression, implying that galectin-3 regulates the expression concentrations of cytokines associated with ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, serum levels of IL-6 and IL-10 were significantly higher in ADHD children compared with healthy controls. However, IL-6 levels did not correlate with the severity of ADHD symptoms [32,33]. In an animal model of ADHD, using spontaneously hypertensive rats (SHR), the serum levels of IL-1α, MCP-1, RANTES, and IP-10 were elevated in five-week-old compared to control rats.…”
Section: Inflammation and The Relationship With Adhdmentioning
confidence: 98%